BRCA1 regulates the cancer stem cell fate of breast cancer cells in the context of hypoxia and histone deacetylase inhibitors - Kim, Hoon (Sci Rep, 2019)
Cancer cell stemness is essential for enabling malignant progression and clonal evolution. Cancer cell fate is likely determined by complex mechanisms involving both cell-intrinsic pathways and stress signals from tumor microenvironment. In this study, we examined the role of the tumor suppressor BRCA1 and hypoxia in the regulation of cancer cell stemness using genetically matched breast cancer cell lines. We have found that BRCA1, a multifunctional protein involved in DNA repair and epigenetic regulation, plays a critical role in the regulation of cancer stem cell (CSC)-like characteristics. Reconstitution of BRCA1 resulted in significant decrease of the CSC-like populations in breast cancer cells whereas down-regulation of BRCA1 resulted in significant increase of the CSC-like populations. Furthermore, the BRCA1-reconstituted tumor cells are more sensitive to the histone deacetylase (HDAC) inhibitor-induced loss of stemness than the BRCA1-deficient cells are. Surprisingly, hypoxia preferentially blocks HDAC inhibitor-induced differentiation of the BRCA1-reconstituted breast cancer cells. In light of the increasing numbers of clinical trials involving HDAC inhibitors in human cancers, our observations strongly suggest that the BRCA1 status and tumor hypoxia should be considered as potentially important clinical parameters that may affect the therapeutic efficacy of HDAC inhibitors.